The Influence of Learning Styles, Attitudes, and Interests on Learning Outcomes in Mathematics Subjects in Elementary Schools - Arni, Yusni; Novitasari, Siska; Nurhaliza, Siti; Sabila, Dita (LPPPIPublishing, 2024)
The study used an experimental method with a quantitative approach. This study has variables (X) namely learning styles, attitudes, and interests and variables (Y) namely learning outcomes in mathematics subjects. This study used a population of all students in the elementary school and one class, namely the experimental class, which was sampled using Purposive Sampling technique. The design used in the one group design, the research subjects were given pre-test and post-test treatment. The data collection technique in this study was a test. And test the instrument by carrying out the validity test and reliability test. The data analysis techniques in this study are using normality, homogeneity, and hypothesis testing. The results of the F test hypothesis test show that if the sig value <0 and F table, then there is a relationship between variable X and variable Y. If the sig value is greater than 0.05 or F count is greater than F table, then there is no impact of variable X on variable Y. In the F test with a value of 19.131 which is greater than 3.89, we can conclude that the relationship between variable X and variable Y together has an important impact. In addition, with a (sig) value of 0.001 which is smaller than 0.05, we can conclude that there is a significant effect of variable X on variable Y simultaneously. Thus, Ha is accepted while Ho is rejected. It can be concluded